Sleep apnoea in the elderly: a great challenge for the future - Osorio, Ricardo S.; Martínez-García, Miguel Ángel; Rapoport, David M. (The European respiratory journal, 2022)
Due in part to overall improvements in health, the population of elderly individuals is increasing rapidly. Similarly, obstructive sleep apnoea (OSA) is both gaining increased recognition and also increasing due to the worldwide obesity epidemic. The overlap of OSA and ageing is large, but there is strong plausibility for causation in both directions: OSA is associated with pathological processes that may accelerate ageing and ageing-related processes; ageing may cause physical and neurological changes that predispose to obstructive (and central) apnoea. In addition, the common symptoms ( e.g. excessive daytime sleepiness, and defects in memory and cognition), possible physiological consequences of OSA ( e.g. accelerated cardiovascular and cerebrovascular atherosclerosis), and changes in metabolic and inflammatory markers overlap with the symptoms and associated conditions seen in ageing. There is also the possibility of synergy in the effects of these symptoms and conditions on quality of life, as well as a need to separate treatable consequences of OSA from age-related complaints. Taken together, the aforementioned considerations make it essential to review the interaction of OSA and ageing, both proven and suspected. The present review examines some aspects of what is known and points to the need for further investigation of the relationships, given the large number of potentially affected subjects.